2021
DOI: 10.1038/s41598-020-79534-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal methods for estimating sports vision in kendo athletes

Abstract: This study investigated whether the eight standard tests of sports vision used in Japan appropriately reflect sports vision; whether all eight tests are necessary; and if not, which combination yields the optimal model. Participants were kendo practitioners (exercise group, n = 41) and those with no exercise habits (non-exercise group, n = 65). The performance of the two groups on all eight tests were compared. The groups differed in static visual acuity, kinetic visual acuity, and eye/hand coordination. A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Age-related decline in KVA has also been observed in young and middle-aged soccer players (n = 44) and in nonathletes of the same age group (n = 45) 25) . Recently, Kudo et al reported kendo players (n = 41; 35.4 ± 15.7 years, range 19-65 years) had significantly higher KVA (p < 0.01) than nonexercisers (n = 65; 38.1 ± 17.1 years, range 19-71 years) 26) .…”
Section: Sports and Age-related Decline Of Kvamentioning
confidence: 97%
“…Age-related decline in KVA has also been observed in young and middle-aged soccer players (n = 44) and in nonathletes of the same age group (n = 45) 25) . Recently, Kudo et al reported kendo players (n = 41; 35.4 ± 15.7 years, range 19-65 years) had significantly higher KVA (p < 0.01) than nonexercisers (n = 65; 38.1 ± 17.1 years, range 19-71 years) 26) .…”
Section: Sports and Age-related Decline Of Kvamentioning
confidence: 97%
“…Additionally, RT has been associated with the ability to quickly assess the position and direction of an object in space ( i.e ., visual perception), however, no link has been reported between RT and kinetic visual acuity and visual field ( Kohmura et al, 2007 ; Mańkowska et al, 2015 ). Both visual skills variables and RT appear as important predictors for estimating sport vision performance ( Kudo et al, 2021 ), cognition in older women ( Anstey, Lord & Williams, 1997 ), driving skills ( Plainis & Murray, 2002 ), and falling prevalence ( Lord et al, 1994 ) indicating their potential co-dependent nature. The relationship between visual skills and RT was neither explored in in-duty military personnel although they are required to be vigilant, fast in decision making and to have maximal concentration during each professional task ( Yanovich et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%